The Relationships Between Physical Performance, Activity Levels, and Falls in Older Men. (1st November 2018) - Orwoll, Eric S; Fino, Nora F; Gill, Thomas M; Cauley, Jane A; Strotmeyer, Elsa S; Ensrud, Kristine E; Kado, Deborah M; Barrett-Connor, Elizabeth; Bauer, Douglas C; Cawthon, Peggy M; Lapidus, Jodi; ,
Abstract: Background: Physical performance and activity have both been linked to fall risk, but the way they are jointly associated with falls is unclear. We investigated how these two factors are related to incident falls in older men. Methods: In 2, 741 men (78.8 ± 5 years), we evaluated the associations between activity and physical performance and how they jointly contributed to incident falls. Activity was assessed by accelerometry. Physical performance was measured by gait speed, dynamic balance (narrow walk), chair stand time, grip strength, and leg power. Falls were ascertained by tri-annual questionnaires. Results: Men were grouped into four categories based on activity and performance levels. The greatest number of falls (36%–43%) and the highest fall rate (4.7–5.4/y among those who fell) (depending on the performance test) occurred in men with low activity/low performance, but most falls (57%–64%) and relatively high fall rates (3.0–4.35/y) occurred in the other groups (low activity/high performance, high activity/high performance and high activity/low performance; 70% of men were in these groups). There were interactions between activity, performance (gait speed, narrow walk), and incident falls ( p = .001–.02); predicted falls per year were highest in men with low activity/low performance, but there was also a peak of predicted falls in those with high activity. Conclusions: In community-dwelling older men, many falls occur in those with the lowest activity/worst physical performance but fall risk is also substantial with better activity and performance. Activity/physical performance assessments may improve identification of older men at risk of falls, and allow individualized approaches to prevention.